137Cs and isotopic ratios of Pu and U in lichens and mosses from Russian Arctic areas - Dutheil, Paul; Paatero, Jussi; Rodushkin, Ilia; Sundström, Timo; Leppänen, Ari-Pekka; Salminen-Paatero, Susanna (Environmental Science and Pollution Research, 2023)
Peer reviewed